Dokumentasi budaya ngaruat lembur di Radio RASI FM - Dian Wardiana Wardiana; Ute Lies Siti Khadijah; Evi Nursanti Rukmana (Jurnal Kajian Informasi dan Perpustakaan, 2018)
Radio RASI FM is a community radio that organizes and broadcasts the tradition of ‘ngaruat lembur’, the tradition of expressing gratitude to God, and to ward off disasters as well. This radio performs documentation starting from data searching to creating a form of cultural documentation. The study purpose was to see the documentation process of the traditional culture of ‘ngaruat lembu’ at RASI FM radio. The research used the case study method through qualitative method approach to the owner, broadcaster of radio and community of Cisewu Village. The study results indicated that RASI FM radio documented the ‘ngaruat lembur’ tradition through the recording and management process. Recording activities started from the collection of information and records in the form of pouring data. Management activities consisted of the distribution of duties as an on-air announcer, off-air broadcaster, and audio-visual documentation. Then, the storage of written broadcast results on radio and data into audio-visual media was performed and preservation of documents through the separation and maintenance of audio-visual media. Based on that, we constructed a model of the cultural documentation process of ‘ngaruat lembur’ on RASI FM radio. The radio serves as a preserver of rural community traditions through the ‘ngaruat lembur’ program, which is followed by all circles of society. However, the radio team did not yet have a digital-based form of audio-visual documentation maintenance. Nevertheless, RASI FM radio has become a forum for transferring traditional information of Cisewu Village community.